1ISG-031 Advanced access programmes and budget impact in a teaching hospital in rome. (March 2019) - Gambarelli, G; Fioravanti, F; de Feo, R; Colaccio, FM; Gambarelli, G; Proli, EM
Abstract : Background: Early access programmes (EAP) are adopted by companies as they offer ethical and controlled mechanisms of access to new drugs for patients with no therapeutic options available, out of clinical trials and before the market launch. These programmes are also known as compassionate use, early access market, special access… The regulation that promotes early access programmes is the (EC)726/2004-Article 83. Each State has its own national regulations. European Medicines Agency (EMA) recommendations assist as guidelines, along with the Prime (PRIority Medicines) that the EMA launched in March 2017 to accelerate the pre-launch of life-saving experimental drugs. Purpose: This study aims to evaluate EAP programmes' budget impact in the years2016 and 2017 in a University Hospital in Rome. Material and methods: We analysed data from the Farmed platform (regional online platform), AIFA's agreements for Compassionate Use (update 18 May 2018), 648/96 Italian law (for special allowed indications) and the use of class C indication for drugs not reimbursed in Italy. A table based on EAP requests during the years 2012–2017 for some drugs (Ibrutinib, Brentuximab, Daratumumab, Brentuximab, Idelasilib, Ledaga, Blincyto) has also been produced. Results: During 2016, Lenvima cpr, Orkambi cpr, Lynparza cpr, distributed in hospital pharmacies, obtained therapeutic indications reimbursed in Italy and had a previously EAP programmes' distribution. Here are drugs, number of patients before reimboursement, estimated budget impact: Lenvima (22 patients, €600, 000/year), Orkambi cpr (15 patients, €1, 200, 000/year) and Lynparza cpr (four patients, €300, 000/year). In 2017, Ibrance cpr, Talz fl and Zynbrita fl, distributed in hospital pharmacies, obtained therapeutic indication reimbursed in Italy. These drugs where in class C for the renegotiation of the price and have managed a special price (€1 per packaging for Ibrance cpr, all dosages) or were delivered as medical samples. Here are drugs, number of patients before reimbursement, estimated annual budget impact: Ibrance cpr (45 patients, €1, 800, 000/year), Talz fl (three patients, €30, 000/year) and Zynbrita fl (15 patients, €150, 000/year, now out of commerce). The additional economic budget impact was 6% for 2016 and 5% for 2017. Conclusion: 2016 and 2017data show how EAPs are a valuable tool for the market introduction of drugs. Tools should be well evaluated during definition of the annual budget since the budget impact is important and affects current economic commitments. The AIFA Compassionate Use List is a useful tool for an overview of the agreements currently used. It can offer valuable help in the management of newly marketed drugs. References and/or acknowledgements: http://www.who.int/mediacentre/news/statement/2014/ebola-ethical-review-summary/en/ http://www.ema.europa.eu/docs/en_GB/document_library/Regulatory_and_procedural_guideline/2009/10/WC500004075.pdf. http://www.mhra.gov.uk/Howweregulate/Innovation/EarlyaccesstomedicinesschemeEAMS/inde.htm. http://www.agenziafarmaco.gov.it/content/farmaci-ad-uso-compassionevole No conflict of interest.